1. substitute y with 2x-6 so the equation is 2(2x-6)-x=3. distribute 4x-12-x=3. combined like terms 3x-12=3. move the -12 to the other side 3x=15. divide x=5. plug x into any equation y=2(5)-6. distribute y=10-6. solve y=4 answer is (5,4)

2. (-x+y=4)

+(-2-y=2)

-3x=6

divide x=-2. plug x into any equation -(-2)+y=4. distribute 2+y=4. move 2 over and solve y=2 answer is (-2,2)

3. (x-2y=2)*2-----> (2x-4y=4)

(3x+4y=3)*1-----> +(3x+4y=3)

5x=7

Divide x=7/5=1 2/5=1.4. plug x into anyequation 3(1.4)+4y=3. distribute 4.2+4y=3. move 4.2 over 4y=-1.2 solve y=-0.3